2010
DOI: 10.1029/2010gl044020
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetry of the magnetic field wrapping pattern in the Venusian magnetotail

Abstract: We examine statistically the magnetic field in the Venusian magnetotail which is formed by the draping of interplanetary magnetic field lines. Although the near‐planet and distant magnetotail regions have been sampled by the various missions to Venus and the general magnetic features of the distant magnetotail are well established, the near wake region from about 1.3 to 3 Venusian radii downstream of the planet remained unexplored until the Venus Express mission. Here we report the unanticipated finding of a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
105
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 19 publications
13
105
0
Order By: Relevance
“…With a three-dimensional model, Kallio et al (2006) showed that asymmetry in the escape of O + was due to the motional electric field, in agreement with Moore et al (1991) . Hybrid simulations are in good agreement with Pioneer Venus Orbiter observations (Jarvinen et al 2008) and Venus-Express observations (Kallio et al 2008;Zhang et al 2010) and reproduce the main boundaries and regions.…”
Section: Hybrid Models Of Venus' Interaction With the Solar Windsupporting
confidence: 69%
“…With a three-dimensional model, Kallio et al (2006) showed that asymmetry in the escape of O + was due to the motional electric field, in agreement with Moore et al (1991) . Hybrid simulations are in good agreement with Pioneer Venus Orbiter observations (Jarvinen et al 2008) and Venus-Express observations (Kallio et al 2008;Zhang et al 2010) and reproduce the main boundaries and regions.…”
Section: Hybrid Models Of Venus' Interaction With the Solar Windsupporting
confidence: 69%
“…In Fig. 1 Zhang et al, 2010). This asymmetry can also be obtained in the Hall-MHD model but not in single-fluid or in multi-species MHD models.…”
Section: Global Plasma and Field Asymmetriesmentioning
confidence: 56%
“…This indicates that the magnetic field is over-draped, bending towards the axis of the tail as was observed e.g. at Venus (Zhang et al, 2010). A schematic of the change between B rad positive and negative can be seen in Fig.…”
Section: Magnetic Field Line Drapingmentioning
confidence: 88%